Small farmer innovations: the drive for efficiency - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Small-scale farmers have always needed to carry out experiments on their farms. This has contributed to, and is the basis of, their indigenous knowledge. They have invariably had a pragmatic approach to development interventions and have often...